Analisis Kepuasan Anggota Pada Credit Union Sehaq Pahauman Kecamatan Sengah Temila Kabupaten Landak - Yulita Yuniati (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of this research is to understand the satisfaction of members of the Credit Union Sehaq Pahauman, Kabupaten Landak. This research is a case study using survey method. Data collection techniques are interviews, questionnaires, observation, and document business. The population was all service users who have used the services Sehaq Credit Union in 2012, amounting to 2,989 people and a sample of 100 people determined that they were taken using purposive sampling technique. Analysis Tool is a Cartesian diagram. Results revealed there is one dimension that is in quadrant A, 9 dimensions are in quadrant B, 7 dimensions are in quadrant C, and 3 dimensions are in quadrant D.